Maternal and Foetal complications in Neglected Transverse LIE - Khattak, Noor Nasir; Majid, Shamim S.; Haleemi, Musarrat; Utman, Naeema (Journal of Postgraduate Medical Institute, 2011)
To see the frequency of foetal and maternal complications o fneglected transverse lie at a tertiary care hospital. This prospective study was conducted at Gyane B unit LRH, Peshawar from First January 1997 to 31st Deceber 1997. Eighty seven patients presenting with neglected transverse lie were included in this stuy detail information regarding name, age, address, parity, past history, physical abdominal and vaginal examination findings. generla management and specific mangements lke internal podalic version, caesarean section, foetal complications and maternal complications of neglected transverse lie were entered into a predesigned proforma for the purpose. Neglected transverse lie is associated with various maternal and foetal complciations prenatal examinations are essential to reduce the unfortunate complications of transverse lie.